Genomic ancestry estimation quantifies use of wild species in grape breeding. (December 2016) - Migicovsky, Zoë; Sawler, Jason; Money, Daniel; Eibach, Rudolph; Miller, Allison; Luby, James; Jamieson, Andrew; Velasco, Dianne; von Kintzel, Sven; Warner, John; Wührer, Walter; Brown, Patrick; et al.
Abstract Background Grapes are one of the world's most valuable crops and most are made into wine. Grapes belong to the genusVitis, which includes over 60 inter-fertile species. The most common grape cultivars derive their entire ancestry from the speciesVitis vinifera, but wild relatives have also been exploited to create hybrid cultivars, often with increased disease resistance. Results We evaluate the genetic ancestry of some of the most widely grown commercial hybrids from North America and Europe. Using genotyping-by-sequencing (GBS), we generated 2482 SNPs and 56 indels from 7 wildVitis, 7 V. vinifera, and 64 hybrid cultivars. We used a principal component analysis (PCA) based ancestry estimation procedure and verified its accuracy with both empirical and simulated data.V. vinifera ancestry ranged from 11 % to 76 % across hybrids studied. Approximately one third (22/64) of the hybrids have ancestry estimates consistent with F1 hybridization: they derive half of their ancestry from wildVitis and half fromV. vinifera . Conclusions Our results suggest that hybrid grape breeding is in its infancy. The distribution ofV. vinifera ancestry across hybrids also suggests that backcrosses to wildVitis species have been more frequent than backcrosses toV. vinifera during hybrid grape breeding. This pattern is unusual in crop breeding, as it is most common to repeatedly backcross to elite, or domesticated, germplasm. We anticipate our method can be extended to facilitate marker-assisted selection in order to introgress beneficial wildVitis traits, while allowing for offspring with the highestV. vinifera content to be selected at the seedling stage.